2022
DOI: 10.1109/access.2022.3216866
|View full text |Cite
|
Sign up to set email alerts
|

Induced Overvoltage Caused by Indirect Lightning Strikes in Large Photovoltaic Power Plants and Effective Attenuation Techniques

Abstract: Indirect Lightning Stroke (ILS) is considered an urgent issue on overall power systems due to its sudden dangerous occurrence. A grid-connected solar Photovoltaic (PV) power plant of 1MW was considered and analyzed using PSCAD/EMTDC software. The effect of grounding grid resistance (R g ) on the induced voltages caused by the indirect strokes was discussed. The Transient Grounding Potential Rise (TGPR) variation with R g was presented and discussed. Four different models were proposed and installed for the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The AGC system receives the frequency and power signals of the grid-connected point of the photovoltaic power station, determines and calculates as required, and sends the power adjustment command to the photovoltaic inverter through the communication unit [15][16][17][18].…”
Section: Retrofit Of Agc Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The AGC system receives the frequency and power signals of the grid-connected point of the photovoltaic power station, determines and calculates as required, and sends the power adjustment command to the photovoltaic inverter through the communication unit [15][16][17][18].…”
Section: Retrofit Of Agc Systemmentioning
confidence: 99%
“…The AGC system receives the frequency and power signals of the grid‐connected point of the photovoltaic power station, determines and calculates as required, and sends the power adjustment command to the photovoltaic inverter through the communication unit [15–18]. Key technical points: The frequency measurement accuracy and frequency sampling period of the existing photovoltaic power station measurement and control devices are mostly unable to meet the fast frequency response requirements.…”
Section: Fast Frequency Response Technology Of Photovoltaic Power Sta...mentioning
confidence: 99%
“…The ATPDraw model SM59/58 represents the station (Synchronous Generator (SG) =1250 MVA/500 kV) [32], [33].…”
Section: A Npp and Main Transformer Station Modelingmentioning
confidence: 99%
“…Some studies have shown an increase of reliability in distribution networks when using EGLAs in the primary of the transformers [21] as long as their protection level is low, i.e., with the lowest possible value of inception voltage, or combined with grounding systems of special characteristics, such as resonant grounding [22,23]. When grounding resistance values are greater than or equal to 5 Ohm, EGLAs perform better in terms of reducing backflow currents [24]. However, the use of these devices presents certain challenges in terms of stochastic operation of the gap discharge ignition and fast forward residual voltage pulses applied to the primary of the protected transformers.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the protection measure used, a study of the effect of a lightning strike must always be performed in which, through modeling and simulation, the effectiveness of the protection scheme is evaluated to verify that the electrical stresses applied to the equipment during lightning events are maintained within their support margins [30,31]. For these studies, adequate modeling of all parts and components, such as line insulators, poles, grounding, transformers, and protection devices, among others, is required, since the reliability of the results depends directly on the quality and accuracy of the models used [24,32].…”
Section: Introductionmentioning
confidence: 99%